Utilizzo dell’intelligenza artificiale in sostituzione o a supporto dell’avvocato: prospettive future e dovere di competenza tecnologica - Parini, Giorgia Anna (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2022)
The law is currently facing various challenges related to technological innovation, in particular the increasing utilization of forms of Artificial Intelligence. It should be noted that the widespread usage of AI systems does not only support professionals in repetitive tasks but even replaces them entirely. This aspect requires some reflection, especially in respect of the performance of activities which have traditionally been reserved to “protected professions”, with further problems related to contractual process and liability. Furthermore, the professional is now required to know the technological tools that can support him in carrying out the assignment in compliance with a duty of technological competence.